Three Pillars of HR Performance: Discipline, Training, and Motivation at PDAM Tirta Ayu, Tegal Regency (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study examines the influence of work discipline, training, and motivation on employee performance at PDAM Tirta Ayu, Tegal Regency. In a public service organization such as PDAM, employee performance is crucial to ensure customer satisfaction and strengthen institutional competitiveness. A quantitative survey method was used with questionnaires distributed to all 115 employees using a saturated sampling technique, as the entire population was included. The independent variables analyzed were work discipline (attitude, compliance with rules, responsibility), training (materials, methods, instructor competence, duration, facilities), and motivation (intrinsic and extrinsic). Employee performance, as the dependent variable, was measured using indicators of work quality, work quantity, teamwork, and problem-solving ability. The data were processed through multiple linear regression to assess simultaneous and partial effects. The research findings revealed that work discipline, training, and motivation each have a positive and significant impact on employee performance, but for training has a positive and insignificant effect, this is shown by the significant results of each significant level for work discipline sig value = 0.000 (<0.05), training sig value = 0.632 (>0.05) and motivation with sig value = 0.000 (<0.05). These results highlight the importance of strengthening employee discipline, implementing well-structured and sustainable training programs, and fostering sustainable motivation strategies. This research provides practical implications for PDAM Tirta Ayu management in designing policies to improve overall employee performance, thereby improving service quality and organizational competitiveness.